Management of panleukopenia in domestic cats at Veterinary Teaching Hospital of Hasanuddin University - Dwijaya, Melkiedek Jeffry; Rell, Fedri (ARSHI Veterinary Letters, 2023)
Feline panleukopenia virus (FPV) is a viral disease with the main causative agent being a virus in the Parvoviridae family, which is highly contagious and can attack young cats that are clinically characterized by leukopenia, vomiting, depression, dehydration, and diarrhea. Clinical examination revealed dehydration, yellow vomiting, and bloody diarrhea. A supportive examination in the form of a rapid test marked by the presence of lines in panels C and T shows positive results for infection with the feline panleukopenia virus. Treatment of FPV cases was carried out with supportive therapy in the form of Ringer lactate fluid, multivitamins combined with imboost, antibiotics in the form of ceftriaxone, and anti-inflammatory drugs in the form of tolfedine for 7 days. The cat’s condition experienced significant improvement and responded well to the treatments given. The patient was discharged on the seventh day with a normal body condition.